2021
DOI: 10.3389/fnagi.2021.717263
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Excitatory Postsynaptic Scaffolding Protein, Shank3, in Human Brain: Effect of Age and Alzheimer’s Disease

Abstract: Shank3 is a postsynaptic scaffolding protein of excitatory synapses. Mutations or variations of SHANK3 are associated with various psychiatric and neurological disorders. We set to determine its normal expression pattern in the human brain, and its change, if any, with age and Alzheimer’s disease (AD)-type β-amyloid (Aβ) and Tau pathogenesis. In general, Shank3 immunoreactivity (IR) exhibited largely a neuropil pattern with differential laminar/regional distribution across brain regions. In youth and adults, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 107 publications
0
15
0
Order By: Relevance
“…Motor centers of the brain include the motor cortex, basal ganglia, thalamus, and cerebellum. These are all areas that strongly express SHANK3 in an isoform-specific manner ( Peça et al, 2011 ; Wang et al, 2014 ) in both mice and human brains ( Wan et al, 2021 ). In a previous study, grooming was shown to occur in another isoform-specific KO of Shank3 , at a stage corresponding to early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Motor centers of the brain include the motor cortex, basal ganglia, thalamus, and cerebellum. These are all areas that strongly express SHANK3 in an isoform-specific manner ( Peça et al, 2011 ; Wang et al, 2014 ) in both mice and human brains ( Wan et al, 2021 ). In a previous study, grooming was shown to occur in another isoform-specific KO of Shank3 , at a stage corresponding to early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on synaptic SHANK3 expression, but SHANK3 does not only localize to synapses but is also expressed in the nucleus ( Grabrucker et al, 2014 ) and the cytoplasm ( Wang et al, 2014 ). However, synaptic SHANK3 expression is best studied and offers a clear structure for analysis, as shown with different SHANK3 antibodies in the literature ( Arons et al, 2012 ; Han et al, 2016 ; Kerrisk Campbell and Sheng, 2018 ; Wan et al, 2021 ). In respect of synaptic localization, the vNterm SHANK3 antibody can offer new insights.…”
Section: Discussionmentioning
confidence: 99%
“…26 10 -5 ) (Figure S12C). These genes * * are associated with autophagy (56,57), protein ubiquitination (58), and synaptic plasticity (59,60), which are well-established biological functions associated with AD. Of note, ZNF385A (p=8.82 10 -1 for next_Aβ) and SUSD6 (p=2.94 10 -2 for next_Aβ) were not * * previously identified as statistically significant DEGs in any of the 7 spatially resolved pathological categories when Aβ and next_Aβ spots were not collapsed (Figure S12D).…”
Section: * *mentioning
confidence: 99%